2013
DOI: 10.2139/ssrn.2211567
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Fees and Mutual Fund Flows: Evidence from a Natural Experiment in the Indian Mutual Funds Market

Abstract: Mutual fund companies typically charge investors distribution fees, such as 12b-1 fees in the United States, which they then use to pay commissions to brokers. We evaluate a major Indian investor protection reform that limited the ability of mutual funds to charge distribution fees to pay broker commissions. We identify the impact of this policy change by comparing funds charging high distribution fees prior to the reform to those charging low distribution fees; we show that trends in asset growth across these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…We also observed that changes in AUM showed a higher drop than changes in gross distributor MF sales and changes in distributor commission D1 Vs D2 - (ΔGSit D1: 1.6(0.00); D2: 1.45(0.005), ΔAUM it D1: 0.27(0.013); D2: 0.16(0.190), ΔCOMMit D1: 1.63(0.000); D2: 1.32(0.000). The results extend the observation of (Anagol et al. , 2013), who did not find any significant effect on mutual fund flows advised by distributors, as they continued to pay upfront commissions even after the ban.…”
Section: Results and Discussion–univariate Analyses And Multivariate ...supporting
confidence: 87%
See 3 more Smart Citations
“…We also observed that changes in AUM showed a higher drop than changes in gross distributor MF sales and changes in distributor commission D1 Vs D2 - (ΔGSit D1: 1.6(0.00); D2: 1.45(0.005), ΔAUM it D1: 0.27(0.013); D2: 0.16(0.190), ΔCOMMit D1: 1.63(0.000); D2: 1.32(0.000). The results extend the observation of (Anagol et al. , 2013), who did not find any significant effect on mutual fund flows advised by distributors, as they continued to pay upfront commissions even after the ban.…”
Section: Results and Discussion–univariate Analyses And Multivariate ...supporting
confidence: 87%
“…Some related studies (e.g. Anagol et al. , 2013, 2017) tried to capture the effect of the ban on mutual fund front load (2009) for equity funds, excluding other types, and did not find any significant effect on mutual fund flows advised by distributors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In India, there have been several instances of mis-selling by insurance companies and mutual funds (Anagol and Kim 2012;Anagol, Cole, and Sarkar 2012;Anagol et al 2013). The response in the case of mutual funds has been to ban upfront commissions as early as 2009.…”
Section: Introductionmentioning
confidence: 99%